Intramyocellular lipid accumulation after sprint interval and moderate-intensity continuous training in healthy and diabetic subjects - Sjoros T; Saunavaar V; Loyttyniemi E; Koivumaki M; Heinonen IHA; Eskelinen JJ; Virtanen KA; Hannukainen JC; Kalliokoski KK (WILEY, 2022)
The effects of sprint interval training (SIT) on intramyocellular (IMCL) and extramyocellular (EMCL) lipid accumulation are unclear. We tested the effects of SIT and moderate-intensity continuous training (MICT) on IMCL and EMCL accumulation in a randomized controlled setting in two different study populations; healthy untrained men (n 28) and subjects with type 2 diabetes (T2D) or prediabetes (n 26). Proton magnetic resonance spectroscopy (H-1 MRS) was used to determine IMCL and EMCL in the Tibialis anterior muscle (TA) before and after a 2-week exercise period. The exercise period comprised six sessions of SIT or MICT cycling on a cycle ergometer. IMCL increased after SIT compared to MICT (P = 0.042) in both healthy and T2D/prediabetic subjects. On EMCL the training intervention had no significant effect. In conclusion, IMCL serves as an important energy depot during exercise and can be extended by high intensity exercise. The effects of high intensity interval exercise on IMCL seem to be similar regardless of insulin sensitivity or the presence of T2D.